(untitled) (Iranian Journal of Kidney Diseases, 2013)
Idiopathic infantile hypercalcemia (IIH) is a rare disorder caused by CYP24A1 loss-of-function mutation, resulting in impaired degradation of 1,25-dihydroxyvitamin D3. Pamidronate, an intravenously administered bisphosphonate, which is a potent inhibitor of bone resorption, has been reported only once for treatment IIH. We present a case of a previously healthy 5-month-old boy with IIH, where calcemia peaked to 5 mmol/L. Treatment with methylprednisone and furosemide had only minor effects; therefore, 2 intravenous infusions of pamidronate (0.6 mg/kg per dose) corrected the serum calcium level to 2.95 mmol/L. Furthermore, CYP24A1 homozygous mutation p.R396W (c.1186c>t) was identified in this patient, confirming the clinical diagnosis of IIH. In conclusion, IIH has a favorable outcome once properly detected and appropriately treated. Pamidronate has a beneficial effect in those patients with IIH where glucocorticoids and furosemide fail to meet the expectations.